2017
DOI: 10.1007/s13312-017-1110-6
|View full text |Cite
|
Sign up to set email alerts
|

Validating neck circumference and waist circumference as anthropometric measures of overweight/obesity in adolescents

Abstract: Neck circumference and waist circumference may be used in clinical practice and epidemiological studies as an index of overweight/ obesity among school-going adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 7 publications
4
28
0
3
Order By: Relevance
“…In view of the above, the Brazilian Metabolic Syndrome Study 26 indicated that NC is being poorly explored in youngsters and, thus, the present work collaborates in this sense, since the anthropometric and lifestyle variables were investigated, compared with the NC of students in different social classes, indicating also the risks that such association can lead to. The NC also positively correlated with BMI, showing it is a good parameter for the evaluation of obesity 6 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In view of the above, the Brazilian Metabolic Syndrome Study 26 indicated that NC is being poorly explored in youngsters and, thus, the present work collaborates in this sense, since the anthropometric and lifestyle variables were investigated, compared with the NC of students in different social classes, indicating also the risks that such association can lead to. The NC also positively correlated with BMI, showing it is a good parameter for the evaluation of obesity 6 .…”
Section: Discussionmentioning
confidence: 79%
“…The use of direct measures to assess nutritional status, such as body mass index and neck circumference 6 , can predict if there is any degree of overweight, allowing the setting of guidelines for intervention against the disease, called obesity. However, in pediatric visits, measurements with other techniques such as observation and classification of obesity, have not yet been implemented, and, in this connection, the present work may contribute to the discussion about the measurement of neck circumference of schoolchildren with different social characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A partir do sangue total anticoagulado com EDTA, foi realizada a extração do DNA, através do método de Assim como previsto, em sua grande maioria (92,30%), indivíduos com uma maior média para CC, estavam com excesso de peso. Patnaik et al (2017) UNIANOVA ajustado por sexo e idade. Valores expressos em média e desvio padrão.…”
Section: Análise Molecular Dos Genes Adipoq Fndc5 E Tmem18unclassified
“…Já para os meninos, esse dado se repete, àqueles com obesidade ou sobrepeso apresentavam médias superiores para CC (80,5±12,7cm) e CP (32,7±2,8) quando comparadas com os eutróficos que expressaram valores de 64,7±8,6cm e 29±2,6, respectivamente para essas variáveis. Dessa forma, o estudo sugere que medidas de CC e CP podem ser utilizadas na prática clínica e estudos epidemiológicos como um índice de sobrepeso/obesidade entre adolescentes em idade escolar(Patnaik et al, 2017).Para as variáveis %G, PAS e PAD, escolares com excesso de peso apresentaram médias significativamente maiores quando comparados com os eutróficos (Tabela 1). Também, nas categorias de risco desses parâmetros, indivíduos com sobrepeso ou obesidade representavam mais da metade.…”
unclassified
“…Basedon WHR, the subjects were classified into two groups, i.e., WHR <0.90 and WHR ≥0.90 (WHO cutoff points). The NC cut-offs for boys and girls were 30.75 cm and 29.75 cm respectively[24].…”
mentioning
confidence: 99%